PENGAWASAN TENAGA KERJA ASING OLEH KANTOR IMIGRASI KELAS I TPI PONTIANAK - Emma, Emerensiana; Azizurrahman, Sy Hasyim; Hermansyah, Hermansyah (Nestor : Tanjungpura Journal of Law, 2025)
Abstract This article aims to analyze the implementation of supervision of foreign workers by the Class I Immigration Office of the Pontianak Immigration Checkpoint and the factors that influence the implementation of such supervision. The research was conducted through a literature study to collect secondary data and through a field study by conducting interviews to collect primary data. The implementation of supervision of foreign workers is carried out through two supervision systems, the first is administrative supervision and the second is field supervision. The factors that influence the implementation of supervision of foreign workers are: the need for renewal of regulations related to the process of registering foreigners in the territory of Indonesia through one door; lack of number of supervisors and communication and coordination in the field; lack of facilities; and lack of community participation. Keywords: Foreign workers; Immigration; Supervision Abstrak Tulisan ini bermaksud untuk menganalisis pelaksanaan pengawasan tenaga kerja asing oleh Kantor Imigrasi Kelas I TPI Pontianak dan faktor-faktor yang mempengaruhi pelaksanaan pengawasan tersebut. Penelitian dilakukan melalui dengan studi kepustakaan untuk mengumpulkan data sekunder maupun melalui studi lapangan dengan melakukan wawancara untuk mengumpulkan data primer. Pelaksanaan pengawasan tenaga kerja asing dilakukan melalui dua sistem pengawasan yang pertama pengawasan administrasi dan kedua pengawasan lapangan. Faktor-faktor yang mempengaruhi pelaksanaan pengawasan terhadap tenaga kerja asing adalah: dibutuhkannya pembaharuan aturan terkait proses pendataan orang asing yang berada di wilayah Indonesia melalui satu pintu; kurangnya jumlah pengawas serta komunikasi dan koordinasi di lapangan; kurangnya jumlah fasilitas; dan kurangnya partisipasi masyarakat. Kata Kunci: Imigrasi; Pengawasan; Tenaga kerja asing